The Geopolitical Concept of Information Warfare in the Russian Social Thought - Yury Vasilyevich Kosov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is considered geopolitical concept of well-known scholars Y.N. Panarin and A.G. Dygin. The main attention is paid to information war and the forming of the new union of state (Eurasian zone). There is the analysis of the concept of the “Eurasian net” that is based on the theory of “net wars”.